(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Pollution in the environment and climate change are major challenges we face today. After yearsof steady growth, the need for human household appliances finally prompted the organic chemical-basedsectors to ramp up output. That’s why pollution is getting so bad because of that. In order to encouragethe chemical industry to be more environmentally sustainability, green chemistry was developed. In 20years, organic chemistry will have changed significantly, thanks to the numerous researchers who havefocused on it and the concepts of green chemistry. Up to this point, waste minimization, safer solvents,energy-efficient design, and the use of renewable feed stocks have all been taken into account in thecontext of organic compound synthesis. This paper provides a concise analysis of how green chemistryideas have been applied to organic chemical production.